Strategi Pembaharuan Pendidikan melalui Pendekatan Fasilitatif, Persuasif, dan Koersif: Studi Kasus di TK Yunico Jambi - Ella Febriyanti; Anissa Yunico Rahmadani; Mohamad Muspawi; Eva Iryani; Raden Ali (Jurnal Ilmiah Dikdaya, 2026)
Educational reform in early childhood education units requires adaptive and systematic change strategies to be able to meet the challenges of modern developments. However, research specifically examining the integration of facilitative, persuasive, and coercive approaches in educational reform in early childhood education units is still relatively limited. This study aims to describe and analyze educational reform strategies through facilitative, persuasive, and coercive approaches at Yunico Kindergarten in Jambi. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews and observations with the principal, teachers, education staff, and parents of students. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results show that the facilitative approach is realized through the provision of learning facilities and infrastructure and improving teacher competency. The persuasive approach is carried out through dialogic communication, providing motivation, and strengthening a collaborative culture. Meanwhile, the coercive approach is implemented through internal regulations, supervision, and performance evaluation to maintain the consistency of the implementation of educational innovations. The integration of these three approaches forms a comprehensive and sustainable educational reform strategy at Yunico Kindergarten in Jambi.